Data on green tea flavor determinantes as affected by cultivars and manufacturing processes - Zhuo-Xiao Han; Mohammad M. Rana; Guo-Feng Liu; Ming-Jun Gao; Da-Xiang Li; Fu-Guang Wu; Xin-Bao Li; Xiao-Chun Wan; Shu Wei (Data in Brief, 2017)
This paper presents data related to an article entitled “Green tea flavor determinants and their changes over manufacturing processes” (Han et al., 2016) [1]. Green tea samples were prepared with steaming and pan firing treatments from the tender leaves of tea cultivars ‘Bai-Sang Cha’ (‘BAS’) and ‘Fuding-Dabai Cha’ (‘FUD’). Aroma compounds from the tea infusions were detected and quantified using HS-SPME coupled with GC/MS. Sensory evaluation was also made for characteristic tea flavor. The data shows the abundances of the detected aroma compounds, their threshold values and odor characteristics in the two differently processed tea samples as well as two different cultivars.